Kreasi Sandal Rajut sebagai Salah Satu Strategi Pengembangan Desa Wisata Berbasis Ekonomi Warga - Setiyani, Rediana; Widhiastuti, Ratieh; Ningrum, Indah Setia (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
Keji Village is one of 35 tourist villages in Semarang Regency, but according to information from the Village Apparatus, it is a tourist village that is difficult to develop. This is because the Pokdarwis, which has been around for a long time, is getting more and more suspended and never carries out any activities. This is because there are no related institutions that work together to conduct training and the like. The biggest obstacle felt was the absence of souvenirs from Keji Village, due to limited natural resources that could be used as basic materials for making souvenirs. Based on observations, it is known that the majority of Keji Village residents are dominated by women, and most of them are unemployed/not yet working. To be able to attract the enthusiasm of the residents in participating in the training, training in making souvenirs that are attractive to women is needed. The objectives of this service activity are (1) increasing public awareness, especially housewives, on the importance of tourism villages; (2) reactivation of existing pokdarwis; (3) provide training and assistance in making beautiful sandals with knitted decorations. The solutions offered are workshops, counseling, and assistance through the Participatory Rural Appraisal (PRA) method. Through training and practice of making knitting sandals, service participants have new skills in the form of knitting and making beautiful sandals. The trainees were inspired to open up business opportunities by doing business in beautiful sandals online.